Financial toxicity in lung cancer - Boulanger, Mary; Mitchell, Carley; Zhong, Jeffrey; Hsu, Melinda (Frontiers in Oncology, 2022)
In the United States, lung cancer is the third most common cancer and the overall leading cause of cancer death. Due to advances in immunotherapy and targeted therapy, 5-year survival is increasing. The growing population of patients with lung cancer and cancer survivors highlights the importance of comprehensive cancer care, including recognizing and addressing financial toxicity. Financial toxicity is a term used to contextualize the negative effects of the costs of cancer treatment in terms of patient quality of life. The American Society of Clinical Oncology (ASCO) Value Framework places emphasis on high-value care as it evaluates cancer treatments “based on clinical benefit, side effects, and improvements in patient symptoms or quality of life in the context of cost”. Prior studies have shown that risk factors for financial toxicity in patients with lung cancer include lower household income or savings, inability to afford basic necessities, higher than anticipated out of pocket expenses, and taking sick leave. Among lung cancer survivors, patients experience increased unemployment and lower wages compared to the general population underscoring the lasting effects of financial toxicity. Financial toxicity is associated with increased psychosocial distress and decreased quality of life, and bankruptcy is an independent predictor of mortality in patients with cancer. Despite the negative implications of financial toxicity on patients, standardized screening practices and evidence-based interventions are lacking. The “COmphrensive Score for financial Toxicity (COST)” tool has been validated for assessing financial toxicity with correlation with health-related quality of life. Further research is needed to understand the utility of incorporating routine screening for financial toxicity into clinical practice and the efficacy of interventions. Understanding the relationship between financial toxicity and quality of life and survival is critical to providing high-value cancer care and survivorship care.